Determination of Mefenamic Acid and Dexametashone in Instant Pegal Linu Herbal Medicine in Kediri by Using UV-Vis Spectro - Sukmawati, Datin An Nisa; Sembiring, Yulia Shara (ALKIMIA, 2021)
Jamu pegal linu is one of the traditional medicinal products that are in great demand by the public, because it can relieve muscle and bone pain, improve blood circulation, strengthen body resistance, and relieve pain all over the body. However, some industry players have added medicinal medicine such as dexamethashone and mefenamic acid in herbal medicine. This study aims to determine the validity of the method in the analysis of dexamethashone and mefenamic acid by UV-Vis spectrophotometry on herbal medicine circulating in Indonesia several markets in Kediri-East Java. The sampling technique used in this study is a purposive sampling method so as to get 5 samples of herbal medicine (A,B,C,D,E). Research begins with determined of wavelength (nm) maximum of dexamethashone and mefenamic acid standard at 200-400 nm and determined of method validation to ensure the accuracy of the method in determining dexamethashone and mefenamic acid levels in the sample. The results of the research showed that the wavelength maximum of mefenamic acid and dexamethashone standard were 288 nm and 245 nm. The method validation showed that this method is good for detect the presence of mefenamic acid and dexamethasone in herbal medicine with the value of the validation parameters, such as linierity of calibration curve of mefenamic acid and dexamethasone weas 0.998, detection limit (LOD) 0.8779 µg/mL and 0.9677 µg/mL ; quantification limit (LOQ) 2.9264 µg/mL and 2.2256 µg/mL; intraday and interday precision of mefenamic acid was expressed by the value of % standard deviation relative (%RSD) was 0.8905 % and 1.0781 %; intraday and interday precision of dexamethasone was expressed by the value of % standard deviation relative (%RSD) was 0.6917 % and 0.8062 %. Respectively; as well as the accuracy expressed in mean % recovery were 101.547 % for mefenamic acid, and 100.576% for dexamethasone. Results analysis of the sample using a validated method showed that only sample A was mefenamic acid positively with concentration was 7.6796 µg/mL. The other hand, sample C,D and E was dexamethashone positively with concentrations were 2.4978 µg/mL, 2.4112 µg/mL and 8.7748 µg/mL.